Achieving peak performance in music : psychological strategies for optimal flow - Sinnamon, Sarah, 1971- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Achieving Peak Performance in Music: Psychological Strategies for Optimal Flow is a unique and comprehensive exploration of flow in music performance. It describes the optimal performance experiences of great musicians and outlines ten psychological steps that can be implemented to facilitate and enhance optimal experience. Achieving Peak Performance in Music reveals strategies used by experts to prepare themselves emotionally, cognitively, and physically for performance. Combining this information with research carried out amongst professional performers and knowledge gained from decades of study and research by psychologists on how to achieve a positive experience, the book guides readers on a pathway towards optimal performance. Using everyday language, it presents invaluable practical guidance and a toolbox of strategies to help with all aspects of performance, including memorization, visualization, focus, performance anxiety, thought management, motivation, and pre-performance routines. Based on psychological research, the book shares practical knowledge invaluable to music students, parents, and amateur and professional musicians. The strategies on performance provided are applicable to every type of performance, from a student exam to a gig or a concert, making Achieving Peak Performance in Music a significant resource for anyone looking to achieve peak performance"--
Music performance -- What flow feels like : how musicians describe being in flow -- How musicians prepare for peak performance : ten steps to flow -- Managing your emotions -- Managing your thoughts -- Motivation -- Concentration & focus -- Mental Practice, Imagery & Visualisation -- Calming the body and mind -- Pre-performance plans -- Putting it all together.
OCLC-licensed vendor bibliographic record.
Keywords: Music -- Performance -- Psychological aspects; PSYCHOLOGY / Applied Psychology; MUSIC / Instruction & Study / General